Teaching teamwork and collaboration: A task-centered clinical design - Morrill, Deborah (Nurse education today, 2018)
Keywords: dept.nur

Examining changes to statewide NP practice in Connecticut - Kazer, M.W.; O'Sullivan, C.K.; Leonard, M. (Nurse Practitioner, 2018)
In 2014, Connecticut legislators eliminated the need for advanced practice registered nurses with 2,000 practice hours to obtain collaborative practice agreements with physicians. This study examined resulting practice changes, barriers, and suggestions for improved implementation of independent practice. Thirteen NPs participated in focus groups to share their experiences and recommendations. © 2018 Wolters Kluwer Health, Inc. All rights reserved.
Keywords: APRNs; Advanced practice registered nurses; Collaborative practice agreements; Connecticut; Female; Focus Groups; Full-practice authority; Humans; Independent practice; Male; Middle Aged; Nurse Practitioners; Practice Patterns, Nurses'; article; dept.nur; female; human; information processing; legislation and jurisprudence; male; middle aged; nurse practitioner; nursing practice; peer-reviewed; psychology; registered nurse

Urticaria multiforme: A case study - Maynard, K. (Journal of the Dermatology Nurses' Association, 2018)
Urticaria multiforme is a rare, hypersensitivity reaction that occurs in infants and small children. Because of its rare occurrence, many providers are unable to accurately identify the rash and associated symptoms to unnecessary laboratory and histological testing or misdiagnosis. This article highlights the case of an 11-month-old female infant with urticaria multiforme. It explores the identification, diagnosis, and current treatment recommendations. © 2018 Dermatology Nurses' Association.
Keywords: Article; Hypersensitivity Reaction; Pediatric Rash; Urticaria Multiforme; amoxicillin; amoxicillin plus clavulanic acid; anamnesis; antibiotic therapy; case report; cefdinir; cetirizine; clinical article; dept.nur; diphenhydramine; face edema; female; foot edema; hand edema; human; infant; otitis media; papule; peer-reviewed; physical examination; priority journal; pruritus; rash; urticaria multiforme

Preventing and alleviating compassion fatigue through self-care: An educational workshop for nurses - Adimando, Andrea (Journal of Holistic Nursing, 2018)
Though various authors have refined and described the concept of compassion fatigue (CF), the overarching features, predisposing factors, and potential consequences remain relatively consistent. Available literature demonstrates that caregivers caring for patients who are chronically ill and/or traumatized are at highest risk for developing CF. Potential consequences for unmitigated CF include physical, emotional, and work-related consequences, all of which can have negative effects on the quality and safety of care and degree of engagement with one’s employer. CF is further exacerbated by exposure to cumulative, unresolved stress and neglect of one’s own emotional needs over time. Caregivers must be knowledgeable on CF’s risk factors, symptoms, and management strategies to decrease its incidence and negative impacts. This article details the creation, execution, and evaluation of an evidence-based practice change project implemented with the goal of increasing knowledge needed to prevent, identify, and alleviate CF in high-risk nurses. The project involved a series of educational workshops containing information on CF’s risk factors, symptoms, and consequences, with a strong emphasis on self-awareness, self-care, and stress management. Pre- and postknowledge tests showed a significant increase in knowledge was achieved via the workshops, and qualitative surveys indicated a high level of participant satisfaction with the program contents, format, and impact.
Keywords: Adult; Burnout, Professional; Compassion Fatigue; Female; Holistic Nursing; Humans; Inservice Training; Male; Middle Aged; Nurses; Quality of Life; Self Care; Surveys and Questionnaires; adult; burnout; caring; compassion fatigue; dept.nur; educators; female; grief/loss/suffering; health and wellness coaching; holistic nursing; human; in service training; male; meditation/mindfulness; middle aged; nurse; nurses; peer-reviewed; prevention and control; psychology; quality of life; questionnaire; self care; stress and coping; stress management/relaxation; trauma/posttrauma

The successful pairing of deliberate practice with reciprocal peer teaching - Maynard, Kristi (Nurse Educator, 2018)
Keywords: dept.nur; peer-reviewed

Peaches and crocs: A story of gratitude for nurses - Resha, Cheryl Ann (American Nurse Today: Insights, 2018)
My story began when I was 49 years young and told I had Stage IV colorectal cancer. That was almost 12 years ago, and today I am one of the fortunate ones—not only has it been almost 12 more years of living, but my oncologist has used the word “cured”. Like most cancer patients and …
Keywords: dept.nur; ⛔ No DOI found

Cup Feeding as a Supplemental, Alternative Feeding Method for Preterm Breastfed Infants: An Integrative Review. - Penny, Frances; Judge, Michelle; Brownell, Elizabeth; McGrath, Jacqueline M (Maternal and child health journal, 2018)
Background The benefits of human milk for the preterm infant are well established. Preterm infants have lower breastfeeding rates and often face breastfeeding challenges. It is important that feeding practices for preterm infants optimize their chances of breastfeeding. Objective The purpose of this integrated review is to synthesize and critically analyze research related to the safety and efficacy of cup feeding as an alternative, supplemental feeding method for breastfed infants. Data Sources The electronic data bases of PubMed, CINAHL and were used to identify studies published in English from 1998- 2017. Design Using inclusion and exclusion criteria, 27 articles were initially assessed. After further screening 19 articles were included in the full review and of these 5 more were excluded. Lastly, an in-depth review of these 14 studies resulted in 2 more exclusions, for a total of 12 studies that met full inclusion and exclusion criteria. Review Methods Studies were examined for information on safety and efficacy of cup feeding as an alternative, supplemental feeding method for preterm breastfed infants. Studies were grouped into categories of outcomes that included (a) safety and physiologic properties; (b) breastfeeding outcomes. Results Use of cup feeding resulted in more stable heart rate and oxygen saturation than bottle feeding with similar weight gain. Additionally, breastfeeding rates were higher at discharge with continued higher rates at 3 and 6 months post-discharge for cup fed infants. Conclusions Premature infants face more breastfeeding obstacles than term infants. The potential for cup feeding as an alternative to bottle-feeding for breast fed preterm infants is positively supported by these results It is fundamentally important for NICU professionals to establish a protocol, education and training for the potential use of this feeding method for this vulnerable population.
Keywords: *Bottle Feeding; *Breast Feeding/mt [Methods]; *Cooking and Eating Utensils; *Enteral Nutrition/mt [Methods]; *Feeding Methods; *Infant, Premature/ph [Physiology]; Alternative feeding; Bottle Feeding; Breast Feeding; Breastfeeding; Cooking and Eating Utensils; Cup feeding; Enteral Nutrition; Enteral Nutrition/is [Instrumentation]; Feeding Methods; Female; Humans; Infant, Newborn; Infant, Premature; Infants; Male; Preterm; bottle feeding; breast feeding; dept.nur; devices; enteric feeding; female; food intake; human; kitchen; male; newborn; peer-reviewed; physiology; prematurity; procedures

Incivility among nursing professionals in clinical and academic environments: emerging research and opportunities - Green, Cheryl (IGI Global, 2018)
Traditionally, nursing is acknowledged as a caring profession and is associated with advocating for others. However, incivility is increasingly occurring amongst nurses, both in the clinical and academic environments, and is causing affected nurses both psychological and physical harm. Incivility Among Nursing Professionals in Clinical and Academic Environments: Emerging Research and Opportunities provides emerging views and consequences surrounding workplace bullying in the healthcare profession including recognizing the signs and symptoms of incivility in the workplace, identifying ways in which affected nurses can seek help, and examining healthy methods of coping with the incivility. Featuring coverage on a broad range of topics such as human resources, therapy, and clinical nursing, this book is ideally designed for nurses, managers, healthcare workers and consumers, hospital and clinical staff, researchers, students, and policymakers.
Keywords: dept.nur

Using case study methodology to explore the role of discrimination in workplace incivility - Green, Cheryl (Journal of National Black Nurses' Association: JNBNA, 2018)
Exclusionary behaviors can be detrimental to the health and well-being of faculty in the workplace. When colleagues are judged by their peers because of the color of their skin, the language they speak, their gender, or who they choose to love (lesbian, gay, bisexual, transgender, asexual, or questioning), affected faculty are left emotionally and physically vulnerable. Institutions of higher learning must set standards of zero tolerance for faculty-to-faculty incivility. With standards taken from each faculty discipline, codes of conduct can be implemented not only at a departmental level, but also throughout the educational system.
Keywords: Discrimination; Exclusionary; Faculty; Humans; Incivility; Interprofessional Relations; Prejudice; dept.nur; peer-reviewed

Complimentary Care: When Our Patients Request to Pray. - Green, Cheryl Ann (Journal of Religion and Health, 2018)
Prayer is viewed in modern medicine as a complimentary alternative treatment. However, to many patients, it is a source of hope and comfort. Patients, when facing illness, advanced disease, disability or death, can benefit from prayer. For healthcare providers, comfort with praying with patients can be deemed as unprofessional conduct or blurred therapeutic boundaries, particularly, when prayer is offered to patients' unsolicited by the patient or their family member(s). Therefore, it is imperative that healthcare providers await the request of prayer by the patient before prayer is initiated.
Keywords: *Attitude of Health Personnel; *Delivery of Health Care; *Faith Healing; *Pastoral Care/mt [Methods]; *Religion; *Spirituality; Attitude of Health Personnel; Delivery of Health Care; Faith Healing; Family; Healthcare providers; Humans; Nurse's Role; Nurses; Pastoral Care; Patients; Prayer; Religion; Religion and Medicine; Spirituality; dept.nur; family; health care delivery; health personnel attitude; human; nurse attitude; pastoral care; peer-reviewed; procedures; religion; spiritual healing

Contemporary issues: The pre-licensure nursing student and medication errors. - Green, Cheryl (Nurse Education Today, 2018)
In Modern health care, the creation of cultures of safety for patients is of the upmost importance. Impacting the institutional stabilization of health care facilities safety initiatives, is the preparation of pre-licensure nursing students to safely administer medications to patients. Therefore, preparation of the pre-licensure nursing student must be evidence-based practice focused and incorporate innovative ways to reduce the potential for medication errors. Copyright © 2018. Published by Elsevier Ltd.
Keywords: *Clinical Competence; *Medication Errors/nu [Nursing]; *Students, Nursing; Clinical Competence; Education, Nursing, Baccalaureate; Humans; Licensure, Nursing; Medication Errors; Medication Errors/pc [Prevention & Control]; Medication errors; Pre-licensure nursing students; Prevention; Students, Nursing; adult; clinical competence; dept.nur; drug safety; editorial; evidence based practice center; health care facility; human; licensing; medication error; nursing; nursing education; nursing student; peer-reviewed; prevention and control

Using instrumentation in psychiatric nursing to assess documentation of the nursing process for emergent non-psychiatric patient events. - Green, Cheryl (Archives of Psychiatric Nursing, 2018)
Ongoing education of experienced psychiatric nurses is imperative given the historically complex health presentations of psychiatric patients. Psychiatric patients tend to have medical co-morbidities and often do not have the financial resources for preventative health care. The hospitalization for acute psychiatric stabilization, is an opportunity for psychiatric nurses to teach and advocate for patients' physiological and psychological health. Documentation of patients' changes in condition and overall clinical presentation, is necessary to ensure patients' health care needs are met. Copyright © 2018 Elsevier Inc. All rights reserved.
Keywords: *Documentation/st [Standards]; *Inservice Training/mt [Methods]; *Nursing Process; *Psychiatric Nursing; Documentation; Educational Measurement; Educational Measurement/sn [Statistics & Numerical Data]; Hospitalization; Humans; Inservice Training; Nurses; Nursing Process; Nursing process; Patients; Psychiatric Nursing; Psychiatry; Surveys and Questionnaires; adult; article; comorbidity; dept.nur; documentation; education; health care need; hospitalization; human; in service training; mental patient; nurse; nursing process; peer-reviewed; procedures; psychiatric nursing; psychological well-being; questionnaire; standards; statistics and numerical data

New nursing faculty and incivility: applying mindfulness-based strategies - Green, Cheryl (Holistic Nursing Practice, 2018)
Workplace incivility remains a problem within the nursing profession. As nurse leaders, we must recognize and not ignore the complexity of cultures that have adapted incivility into the work environment. Nursing education is a discipline that requires collaborative team work, independent drive, and commitment. New nursing faculty experiencing incivility can use mindfulness-based meditation approaches to cope with uncivil behaviors experienced within the workplace. Nurse educators applying the concepts of mindfulness can learn how to provide themselves self-care by reducing stress, as enhanced daily awareness of peace and calm are incorporated into their lifestyle. Mindfulness provides a realization that control can only be given to other persons when an individual allows or accepts another's negative behaviors. Awareness of the value and importance of oneself can assist the nurse educator experiencing incivility to maintain his or her emotional, physical, and spiritual health despite the volatility of the work environment.
Keywords: Attitude of Health Personnel; Bullying; Faculty, Nursing; Humans; Incivility; Interprofessional Relations; Mindfulness; Stress, Psychological; Universities; Workplace; academia; adult; awareness; bullying; complication; dept.nur; etiology; female; health personnel attitude; human; human experiment; incivility; leadership; lifestyle; male; meditation; mental stress; mindfulness; nursing education; nursing faculty; occupation; organization and management; peer-reviewed; psychology; public relations; self care; standards; stress; teamwork; trends; university; work environment; workplace

What is the evidence for use of a supplemental feeding tube device as an alternative supplemental feeding method for breastfed infants? - Penny, Frances; Judge, Michelle; Brownell, Elizabeth; McGrath, Jacqueline M. (Advances in Neonatal Care, 2018)
Background: According to the Healthy People 2020 goals, the sustainability of breastfeeding duration rates within the United States has not been achieved. To increase these rates, it is important that women with breastfeeding difficulties receive the support needed to continue breastfeeding. When supplementation occurs, it is essential that the breastfeeding relationship be preserved. Various methods of supplementation are often recommended including use of the supplemental feeding tube device (SFTD). Purpose: The question guiding this brief is “What evidence exists to support the use of an SFTD as a method of supplementation for breastfed infants?” Search Strategy: The PubMed and CINAHL databases were queried for original research published in English from 1990 through July 2016. Search terms included “supplemental feeding tube,” “breastfeeding,” “term infants,” “premature infants,” “Supplemental Nursing System,” “Lact-aid,” and “supply line.” Findings: Very limited research exists on the use of SFTDs as a method of supplementation for breastfed infants; however, existing research suggests that an SFTD may be useful as a supplementation method for breastfed infants. High-quality research is needed to evaluate the efficacy of using an SFTD for supporting exclusive and all breastfeeding rates. Implications for Practice: Nurses and providers need to be educated and trained in the use of SFTDs as well as all supplemental feeding methods. Information on efficacy and SFTD use should also be included in policies related to breastfeeding and human milk use. Implications for Research: Further research should determine best methods of supplementation for breastfed infants and should examine differences in breastfeeding rates when using the SFTD for supplementation.
Keywords: Breast Feeding; Breastfeeding; Dietary Supplements; Enteral Nutrition; Humans; Infant, Newborn; Nursing Care; Treatment Outcome; breast feeding; breastfeeding support; breastmilk; dept.nur; dietary supplement; enteric feeding; human; human milk; newborn; newborn intensive care; nursing care; peer-reviewed; preterm infant; procedures; supplemental feeding; supplemental feeding device; treatment outcome

Understanding the complexities of the effects of incivility on the victim and using mindfulness to heal - Green, Cheryl Ann (International Journal of Health, Wellness & Society, 2018)
The complexity of the human body is such that any disturbances to its homeostatic state, unreversed, can lead to the development of illness or disease. When one considers the terminology of incivility as a concept, one does not automatically equate this concept with disease or illness. However, incivility left to persist in work environments can prove mentally and physically damaging to the victim. Mindfulness can be used as a means to help nurses experiencing workplace incivility, to begin the process of emotional and physical healing.
Keywords: EMOTIONS (Psychology); HOMEOSTASIS; Illness; Incivility; MINDFULNESS; Mindfulness; NURSES; Nurses; WORK environment; Work Environment; dept.nur; peer-reviewed

Evaluation of the McMahon Competence Assessment Instrument for use with midwifery students during a simulated shoulder dystocia - McMahon, Erin; Jevitt, Cecilia; Aronson, Barbara (Journal of Midwifery & Women's Health, 2018)
IntroductionIntrapartum emergencies occur infrequently but require a prompt and competent response from the midwife to prevent morbidity and mortality of the woman, fetus, and newborn. Simulation provides the opportunity for student midwives to develop competence in a safe environment. The purpose of this study was to determine the inter-rater reliability of the McMahon Competence Assessment Instrument (MCAI) for use with student midwives during a simulated shoulder dystocia scenario. MethodsA pilot study using a nonprobability convenience sample was used to evaluate the MCAI. Content validity indices were calculated for the individual items and the overall instrument using data from a panel of expert reviewers. Fourteen student midwives consented to be video recorded while participating in a simulated shoulder dystocia scenario. Three faculty raters used the MCAI to evaluate the student performance. These quantitative data were used to determine the inter-rater reliability of the MCAI. ResultsThe intraclass correlation coefficient (ICC) was used to assess the inter-rater reliability of MCAI scores between 2 or more raters. The ICC was 0.86 (95% confidence interval, 0.60-0.96). Fleiss's kappa was calculated to determine the inter-rater reliability for individual items. Twenty-three of the 42 items corresponded to excellent strength of agreement. DiscussionThis study demonstrates a method to determine the inter-rater reliability of a competence assessment instrument to be used with student midwives. Data produced by this study were used to revise and improve the instrument. Additional research will further document the inter-rater reliability and can be used to determine changes in student competence. Valid and reliable methods of assessment will encourage the use of simulation to efficiently develop the competence of student midwives.
Keywords: Article; Clinical Competence; Dystocia; Education, Nursing; Educational Measurement; Female; Humans; Infant, Newborn; McMahon Competence Assessment Instrument; Midwifery; Nurse Midwives; Observer Variation; Pilot Projects; Pregnancy; Reproducibility of Results; Shoulder; Simulation Training; Video Recording; assessment; clinical competence; competence; content validity; controlled study; correlation coefficient; dept.nur; dystocia; education; evaluation; expert system; female; human; instrument; intrarater reliability; midwife; midwifery education; midwifery student; newborn; nurse midwife; nursing education; observer variation; obstetric procedure; peer-reviewed; pilot study; pregnancy; priority journal; procedures; quantitative analysis; quantitative study; reliability; reproducibility; scoring system; shoulder; shoulder dystocia; simulation; simulation training; standards; teacher; validation study; validity; videorecording